(untitled) (Alternautas, 2022)
The one-year anniversary of Hurricane Maria calls into question the temporality of disaster, both in terms of lived experience and analysis. It was difficult for Puerto Ricans to mark the first anniversary while so many still live Maria’s daily effects physically, emotionally, and financially. Failing institutions and disaster recovery initiatives have too often deepened vulnerability in the wake of Hurricanes Irma and Maria, thus augmenting the confused sense of pre- and post-disaster. During a September Rutgers University symposium on the “Aftershocks of Disaster: Puerto Rico a Year after Maria,” anthropologist Yarimar Bonilla suggested that perhaps Hurricane Maria was the “aftershock” itself, the culmination of over a century of colonial-capitalist exploitation and layered traumas. If Hurricane Maria was the aftershock, how can we think about disaster and disaster capitalism? Naomi Klein’s The Battle for Paradise: Puerto Rico Takes on the Disaster Capitalists (2018) is a helpful starting point.